ANALYSIS STRATEGY RIAU UNIVERSITY ORGANIZATION IN HUMAN RESOURCE DEVELOPMENT (A CASE STUDY DEVELOPMENT UNIVERSITY LECTURERS RIAU) - Yetri, Arni; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
As educational staff in University of Riau (UR), a Lecturers has duty to implement the three of higher education responsibility. Particularly in teaching, a lecture must have education background . Infact, almost eductional background of lecturers in University of Riau are master degres (S2). To be a lecturer in University of Riau, a lecturer should be have doctoral degree (S3) in other to achieve vision and mission of the university and also society trust UR to study there. From the result can be obtained that the education development strategy to continue lecturer’s study is not did seriously. It can be indicated by their role to give information tranparently about scholarship fund from cooperation parties as DIKTI and Local Goverment of Riau Province. Another reason is no budget allocation to help lecturer to continue their study. We can take an example when the lecturer need a fund as tickets to go abroad and back. UR is not provide funds for it. Besides, there is no cooperation of units in UR to negotiated to improve lecturer education. What happens is partial that cause no place to coordinate each other, share,or making strong strategies to developped lecturer. UR has given a fund seriously for researcher to developt their self. There are many available grant for lecturer to do research, but it is need activeness and seriousness to submit their proposal. Here, there are competiton to obtain the grant research. Keywords: strategy, education, research, lecture.